Ethanolic extract of Halymenia durvillei induced G2/M arrest and altered the levels of cell cycle regulatory proteins of MDA-MB-231 triple-negative breast cancer cells - Rapeewan Settacomkul; Kant Sangpairoj; Suttinee Phuagkhaopong; Krai Meemon; Nakorn Niamnont; Prasert Sobhon; Pornpun Vivithanaporn (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: The GC-MS analysis reported n-hexadecanoic acid or palmitic acid as a major component of the ethanolic extract of Halymenia durvillei (HDET). This compound shows cytotoxic effects against various human cancer cells. The present study investigated the effect of HDET on the viability and proliferation of MDA-MB-231, a triple-negative breast cancer (TNBC) cell line. Experimental approach: Cell proliferation and cell cycle analysis were determined by flow cytometry and cell cycle regulatory protein expression levels were then determined by Western blotting. The presence of reactive oxygen species (ROS) was evaluated by dichlorofluorescein, followed by analyzing changes in gene expression of antioxidant enzymes using a real-time polymerase chain reaction. Findings/Results: HDET dose-dependently reduced cell viability with the 50% inhibitory concentration (IC50) of 269.4 ± 31.2 µg/mL at 24 h. The cell proliferation assays showed increased succinimidyl ester fluorescent intensity after treatment with ≥ 100 µg/mL of HDET, indicating the inhibition of cell proliferation. Cell cycle analysis using propidium iodide staining showed an increased percentage of cells in the G2/M phase. HDET also decreased the levels of cell cycle regulatory proteins including cyclin D1 and increased the level of p21. HDET promoted oxidative stress by increasing ROS levels along with the reduction of catalase expression. However, HDET did not induce apoptosis and caspase activation in TNBC cells. Conclusion and implications: These findings suggest that HDET which is rich in palmitic acid may serve as a potential therapeutic agent to target TNBC via arrest cell cycle progression at the G2/M phase.